Studies in Pedagogy – Traces of the Past and Future Prospects: Book of Abstracts / International Conference, Maribor, 26.-27. 10. 2017 (University of Maribor Press, 2018)
1986 is the year when the Academy of Pedagogy at the University of Maribor became the Faculty of Education. Parallelly, an ambition to establish an independent study programme of Pedagogy in Maribor began to grow. This ambition was achieved in 1997, when the first students of the double-subject programme of Pedagogy enrolled at the then Faculty of Education. When the former Faculty of Education split into three independent institutions in 2006, the Department of Pedagogy became part of the newly founded Faculty of Arts at the University of Maribor, and now, in 2017, the studies in Pedagogy in Maribor celebrate their 20th anniversary. At this occasion the Department of Pedagogy at the Faculty of Arts in Maribor organized on 26th and 27th October 2017 a symposium titled Studies in Pedagogy – Traces of the Past and Future Prospects. The former and current PhD students as well as members of the Department and colleagues from the ex-Yugoslav countries were invited to participate. Their papers are presented in this book in the form of abstracts.